Morte: a crise ante a morte e a reconfiguração da identidade religiosa do adulto na sociedade contemporânea. - Silva, Vania Maria Ferreira (2009)
The present report has the objective to identify thoughts and feelings of people toward death, searching to understand how this crisis interferes in the adult religious identity. The essay aims to identify how crisis facing death interferes in the religious identity reconfiguration of researched adults, as well as, to find out if among those feelings there is a fear related to death and the after death situation. This research uses a qualitative approach of data, once, one does not intend to generalize results. It is used the phenomenological method from this perspective, to identify the meaning of feelings undergone by adults due to death crisis. We collect data from semi-structured interviews with two main questions for the proposed objectives. The sample is of twelve persons from 54 to 90 years old, that say to be Catholic Spirit, Evangelic, no defined Religion and some self-defined with new religious denominations, created at the moment of the interview. The qualitative analysis of experiences and representations is carried out with the data seeking to delimitate the interview content phenomenological description in meaning units, to confront them with based upon theories. The results of the analysis show that adults go through crisis situation when facing death, they tend to question their religious values, developing attitudes that are reflected in their religious identity reconfiguration: some of them withdrawing themselves or completely breaking the affective ties that link them to their religious institutions, others, differently, get closer and intensify ones relations with those institutions or religious groups. And others at home have a holy place, going from the inherited faith to an inner faith, that it is reflected in daily life, so, one can conclude that, an existential crisis happens, when facing death.